2021
DOI: 10.3390/ani11040923
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nitrocompounds in Inhibition of Foodborne Bacteria, Parasites, and Methane Production in Economic Animals

Abstract: Nitrocompounds are derivatives of hydrocarbons, alcohols, fatty acids, and esters, consisting one or more nitro functional groups. Either natural sources of nitrocompounds or synthetic chemicals have been applied in animal diets to investigate their effects on economic animals, since conjugates of 3-nitropropanol and 3-nitropropionic acid were isolated from Astragalus oblongifolius. In this review, emphasis will be placed on nitrocompounds’ antimicrobial activity, toxicity, metabolisms and mechanisms of action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Similar to the results of the current study, several prior studies found that methane production markedly reduced with the supplementation of 3NPA [ 3 , 8 , 16 , 27 ]. Supplementation of 3NPA could inhibit methanogens directly [ 38 ] or competing with the electrons available for methanogens via suppressing ability of formate dehydrogenase in the rumen [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ], which could be an explanation for this phenomenon; although, there was no information pertaining to the rumen methanogens composition and function in the current study. In addition, H 2 accumulation in the cultures treated with 8 and 16 mM 3NPA in both yak and cattle were greater compared to the control (0 mM).…”
Section: Discussionmentioning
confidence: 89%
“…Similar to the results of the current study, several prior studies found that methane production markedly reduced with the supplementation of 3NPA [ 3 , 8 , 16 , 27 ]. Supplementation of 3NPA could inhibit methanogens directly [ 38 ] or competing with the electrons available for methanogens via suppressing ability of formate dehydrogenase in the rumen [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ], which could be an explanation for this phenomenon; although, there was no information pertaining to the rumen methanogens composition and function in the current study. In addition, H 2 accumulation in the cultures treated with 8 and 16 mM 3NPA in both yak and cattle were greater compared to the control (0 mM).…”
Section: Discussionmentioning
confidence: 89%
“…As reviewed by Teng and Kim [ 37 ], certain short-chain nitrocompounds have been reported to exert antimicrobial activity against a variety of microbes and their biological activities. While ethyl nitroacetate exhibited quite modest antimicrobial activity against E. coli O157:H7 and S. Typhimurium, it was very potent at modulating methane production.…”
Section: Discussionmentioning
confidence: 99%
“…However, with longer feeding times, ion carriers could develop resistance in some bacteria ( Vendramini et al, 2016 ) and have therefore been banned in many countries. The addition of methanogenic inhibitors such as nitro derivatives, on the other hand, though could reduce CH 4 production via rumen microbiome alteration, but there are very few reports on their safety assessment ( Teng and Kim, 2021 ).…”
Section: Introductionmentioning
confidence: 99%